GLIM criteria for the diagnosis of malnutrition – A consensus report from the global clinical nutrition community*. Issue 1 (28th March 2019) - Cederholm, T.; Jensen, G.L.; Correia, M.I.T.D.; Gonzalez, M.C.; Fukushima, R.; Higashiguchi, T.; Baptista, G.; Barazzoni, R.; Blaauw, R.; Coats, A.J.S.; Crivelli, A.N.; Evans, D.C.; et al.
Summary: Rationale: This initiative is focused on building a global consensus around core diagnostic criteria for malnutrition in adults in clinical settings. Methods: In January 2016, the Global Leadership Initiative on Malnutrition (GLIM) was convened by several of the major global clinical nutrition societies. GLIM appointed a core leadership committee and a supporting working group with representatives bringing additional global diversity and expertise. Empirical consensus was reached through a series of face‐to‐face meetings, telephone conferences, and e‐mail communications. Results: A two‐step approach for the malnutrition diagnosis was selected, i.e., first screening to identify "at risk" status by the use of any validated screening tool, and second, assessment for diagnosis and grading the severity of malnutrition. The malnutrition criteria for consideration were retrieved from existing approaches for screening and assessment. Potential criteria were subjected to a ballot among the GLIM core and supporting working group members. The top five ranked criteria included three phenotypic criteria (weight loss, low body mass index, and reduced muscle mass) and two etiologic criteria (reduced food intake or assimilation, and inflammation or disease burden). To diagnose malnutrition at least one phenotypic criterion and one etiologic criterion should be present. Phenotypic metrics for grading severity as Stage 1 (moderate) and Stage 2 (severe) malnutrition are proposed. It is recommended that the etiologic criteria be used to guide intervention and anticipated outcomes. The recommended approach supports classification of malnutrition into four etiology‐related diagnosis categories. Conclusion: A consensus scheme for diagnosing malnutrition in adults in clinical settings on a global scale is proposed. Next steps are to secure further collaboration and endorsements from leading nutrition professional societies, to identify overlaps with syndromes like cachexia and sarcopenia, and to promote dissemination, validation studies, and feedback. The diagnostic construct should be re‐considered every 3–5 years.